Case Report: A patient presenting primarily with psychosis of NPSLE treated with telitacicept, corticosteroids, and immunosuppressants - Xie, Wei; Chen, Peijue; Luo, Lili (Frontiers in Immunology, 2025)
Therapeutic strategies for neuropsychiatric systemic lupus erythematosus (NPSLE) primarily target underlying pathogenic mechanisms and typically include corticosteroids, immunosuppressants, anticoagulation, and adjunctive treatments. B-cell–targeted biologics are an emerging option for NPSLE. Although telitacicept is approved for systemic lupus erythematosus (SLE) treatment in China, evidence supporting its use in NPSLE remains limited. This case report presents a 20-year-old female diagnosed with NPSLE who exhibited psychotic symptoms as the predominant manifestation and was treated with telitacicept, corticosteroids, and immunosuppressants. During the treatment period, her psychiatric symptoms remained in remission without infections or adverse events. Her disease activity score (SLEDAI-2000) declined from 23 to 2.